Could Cerebrospinal Fluid Biomarkers Offer Better Predictive Value for Spinal Cord Ischaemia Than Current Neuromonitoring Techniques During Thoracoabdominal Aortic Aneurysm Repair - A Systematic Review - Harky,Amer (2019)
Abstract Objective: Cerebrospinal fluid (CSF) drainage is a technique that has significantly reduced the incidence of spinal cord ischaemia (SCI). We present results of a systematic review to assess the literature on this topic in relation to thoracoabdominal aortic aneurysm repair (TAAR). Methods: Major medical databases were searched to identify papers related to CSF biomarkers measured during TAAAR. Results: Fifteen papers reported measurements of CSF biomarkers with 265 patients in total. CSF biomarkers measured included S-100ß, neuron-specific endolase (NSE), lactate, glial fibrillary acidic protein A (GFPa), Tau, heat shock protein 70 and 27 (HSP70, HSP27), and proinflammatory cytokines. Lactate and S-100ß were reported the most, but did not correlate with SCI, which was also the case with NSE and TAU. GFPa showed significant CSF level rises, both intra and postoperative in patients who suffered SCI and warrants further investigation, similar results were seen with HSP70, HSP27 and IL-8. Conclusions: Although there is significant interest in this topic, there still remains a significant lack of high-quality studies investigating CSF biomarkers during TAAR to detect SCI. A large and multicentre study is required to identify the significant role of each biomarker.